Construcción de materiales de apoyo didáctico para desarrollar destrezas de comprensión lectora en el área de Lengua y Literatura para el cuarto grado de educación general básica, de la unidad educativa fiscal mixta “Marieta de Veintimilla” de la ciudad de Loja periodo 2013 – 2014 - Espinosa Orellana, Nelly Alexandra (2015)
This research paper entitled: "BUILDING MATERIALS EDUCATIONAL SUPPORT FOR DEVELOPING READING SKILLS OF UNDERSTANDING IN THE AREA OF LANGUAGE AND LITERATURE FOR THE DEGREE OF BASIC FOURTH GENERAL EDUCATION OF EDUCATIONAL MIXED FINANCIAL UNIT" Marieta de Veintemilla "CITY LOJA PERIOD 2013 - 2014 ", has the general objective, qualitatively Contribute to the development and proper use of teaching support material, by the teachers, which lead to the development of reading comprehension skills in the area of Language and Literature, children in the fourth year of General Basic Education of the Education Unit "Marieta de Veintemilla" city of Loja 2013-2014 school. And Identify specific objective teaching aids in order to develop reading comprehension skills in the area of Language and Literature; The methodology used; the scientific methods, inductive, analytical descriptive. The technique used was bibliographic collection, the structured interview, the survey of three teachers and 65 children from the ages of basic general education rooms the total population was 68 investigated the same that allowed the current status of reading comprehension skills by teachers to impart their knowledge in the area of Language Arts. So I can conclude 100% of teachers do not use in a manner suitable teaching support materials to develop reading comprehension skills